Chemokine Receptor CCR2b Enhanced Anti-tumor Function of Chimeric Antigen Receptor T Cells Targeting Mesothelin in a Non-small-cell Lung Carcinoma Model - Wang, Yanan; Wang, Jing; Yang, Xinyi; Yang, Jinlong; Lu, Panpan; Zhao, Lin; Li, Bokang; Pan, Hanyu; Jiang, Zhengtao; Shen, Xiaoting; Liang, Zhiming; Liang, Yue; et al. (Frontiers in Immunology, 2021)
Chimeric antigen receptor (CAR) T cell therapy faces a number of challenges for the treatment of non-small-cell lung carcinoma (NSCLC), and efficient migration of circulating CAR T cells plays an important role in anti-tumor activity. In this study, a chimeric antigen receptor specific for tumor antigen mesothelin (Msln-CAR) was co-expressed with cell chemokine receptors CCR2b or CCR4. Findings show that CCR2b and CCR4 enhanced the migration of Msln-CAR T cell in vitro by transwell assay. When incubated with mesothelin-positive tumor cells, Msln-CCR2b-CAR and Msln-CCR4-CAR T cell specifically exerted potent cytotoxicity and produced high levels of proinflammatory cytokine, including IL-2, IFN-γ and TNF-α. Furthermore, NSCLC cell line-derived xenograft (CDX) model was constructed by implanting subcutaneously modified A549 into NSG mice. Compared to conventional Msln-CAR T cells, living imaging indicated that Msln-CCR2b-CAR T cells displayed superior anti-tumor function due to enhanced migration and infiltration into tumor tissue shown by immunohistochemistry (IHC) analysis. In addition, histopathological examinations of mice organs showed that no obvious organic damages were observed. This is the first time that CAR T cell therapy combined with chemokine receptor is applied to NSCLC treatment.